PHLiPPing the Switch on Akt and Protein Kinase C Signaling - Brognard, John (2008)
The Ser/Thr specific-phosphatase PHLPP (Pleckstrin Homology (PH) domain leucine-rich repeat protein phosphatase) provides “the brakes” for Akt and protein kinase C (PKC) signaling. The two isoforms of this recently discovered family, PHLPP1 and PHLPP2, control the amplitude and duration of signaling of Akt and PKC by catalyzing the dephosphorylation of the hydrophobic phosphorylation motif, a C-terminal phosphorylation switch that controls the activity of these kinases. Aberrant regulation of either kinase accompanies many diseases, notably diabetes and cancer. By specifically dephosphorylating the hydrophobic motif, PHLPP controls the degree of agonist-evoked signaling by Akt and the cellular levels of PKC. This review focuses on the function of PHLPP1 and PHLPP2 in modulating signaling by Akt and PKC.